Investigation on the erosive wear resistance of squeeze cast AA7150 under slurry conditions. (2020) - Thiyagesan, G.; Vigneshwaran, S.; Mohammed, S. Beer; Srinivasan, S.A.; Thirumaran, B.; Babu, S.P. Kumaresh
Abstract: An investigation has been performed on the slurry erosion behavior of squeeze cast AA7150 aluminium alloy – a potential structural alloy in as cast condition. The tests were conducted at room temperature varying the service factors using quarts silica sand. The cast samples were examined for its metallurgical and mechanical factors followed by investigation on erosive wear behavior. The results showed the ductile nature of mechanism undergone and greater influence was seen with respect to the angle of impingement. The erodent flow rate also significantly affects the performance of the material. The surface morphologies of the wear tested specimens were examined using SEM for better understanding on the mechanism of failure. Severe plastic deformation is seen in all the cases as the strain energy exceeded the elastic strain rate.